The Pengaruh Profitability Dan Fixed Tangible Assets Terhadap Leverage Pada Perusahaan Manufaktur 2018-2020 - Putri Dwi Ariska; Dwi Ermayanti Susilo (Forum Kerjasama Pendidikan Tinggi, 2022)
In determining leverage, there are several factors considered by companies in general, including profitability and fixed tangible assets. Profitability is the profit earned by the company in a certain period. Fixed tangible assets are assets that are owned and used to operate and have future benefits for more than one budget period and are not intended for sale. This study aims to determine the effect of profitability and fixed tangible assets on leverage in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This study uses quantitative methods, namely research based on the philosophy of positivism, which is used to examine certain populations or samples, collect data, and analyze statistical data. The population of this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The number of samples of 57 companies was selected through purposive sampling. Methods of collecting data through financial management books, journals about leverage, financial reports. The results show that profitability has no significant positive effect on leverage. Fixed tangible assets have no significant positive effect on leverage.